(untitled) (Bangladesh Agronomy Journal, 2018)
The experiment was conducted at charland of Charsadipur in Pabna district under AEZ-11 during Khrif season of 2014 and 2015 to determine appropriate fertilizer dose for enhancing yield of blackgram as well as to increase farmers’ income. The experiment was laid out in a randomized complete block design with four dispersed replications. Eight fertilizer packages, viz.T1: N20P15K6S9Zn2 kg ha-1(STB), T2: N25P15K6S9Zn2kg ha-1, T3: N25P19K6S9Zn2 kg ha-1, T4: N25P15K8S9Zn2 kg ha-1, T5: N20P19K8S9Zn2 kg ha-1, T6: N25P19K15S9Zn2 kg ha-1, T7: N15P11K5S7Zn1.5kg ha-1and T8: Native nutrients (control) were tested on blackgram. Fertilizer package of N25P19K15S9Zn2 kg ha-1 (T6) enhanced crop growth and yield of blackgram in both the years. Maximum seed yield of blackgram (1.43t ha-1 in 2014 and 0.97 t ha-1 in 2015) was obtained with N25P19K15S9Zn2 kg ha-1 (T6), which was 80 and 147% more than the control in 2014 and 2015, respectively. The highest gross return (Tk. 82815 ha-1 in 2014 and Tk. 65200 ha-1 in 2015) and gross margin (Tk. 51125 ha-1 in 2014 and Tk. 32020 ha-1 in 2015) were also recorded from the same treatment in both the years. The results revealed that fertilizer package of N25P19K15S9Zn2kg ha-1 might be recommended for getting higher seed yield of blackgram and economic return as well under charland condition of Pabna district Bangladesh Agron. J. 2018, 21(1): 89-94